Challenges and Solutions for Applying the Travel Cost Demand Model to Geographically Remote Visitor Destinations: A Case Study of Bear Viewing at Katmai National Park and Preserve. Issue 6 (2nd November 2017) - Richardson, Leslie; Huber, Christopher; Loomis, John
ABSTRACT: Remote and unique destinations present difficulties when attempting to construct traditional travel cost models to value recreation demand. The biggest limitation comes from the lack of variation in the dependent variable, defined as the number of trips taken over a set time frame. There are various approaches that can be used for overcoming limitations of the traditional travel cost model in the context of remote destinations. This study applies an adaptation of the standard model to estimate recreation benefits of bear viewing at Katmai National Park and Preserve in Alaska, which represents a once-in-a-lifetime experience for many visitors. Results demonstrate that visitors to this park's Brooks Camp area are willing to pay an average of US287 per day of bear viewing. Implications of these findings for valuing recreation at other remote destinations are discussed.